Occupational outcomes of people with multiple sclerosis during the COVID-19 pandemic: a systematic review with meta-analysis - Vitturi, Bruno Kusznir; Rahmani, Alborz; Montecucco, Alfredo; Dini, Guglielmo; Durando, Paolo (Frontiers in Public Health, 2023)
People with Multiple Sclerosis (PwMS) are vulnerable to unfavourable occupational outcomes and the COVID-19 pandemic brought major consequences on people's professional lives. In this view, we decided to investigate the occupational outcomes of PwMS during the COVID-19 pandemic.We performed a systematic review with meta-analysis searching key terms in four databases. We initially included any peer-reviewed original article that enrolled adult patients with the diagnosis of MS and assessed any occupational variable during the COVID-19 pandemic. There were no time limits and no language restrictions. The primary outcomes were the prevalence of unemployment, retirement and employment status change among people with MS during the COVID-19 pandemic. Other outcomes included the modality and characteristics of work: type of work, full-time work, part-time work and remote work. We also searched for data from studies that addressed any change in the work status due to the COVID-19 outbreak.We identified 49 eligible articles comprising a total sample size of 17364 individuals with MS. The pooled prevalence of unemployment and retirement was 0.47 (95% CI = 0.42 -0.53). The pooled prevalence of PwMS who were unemployed or retired was positively associated with the progressive phenotype of the disease (p = 0.017) and the use of glatiramer acetate (p = 0.004), but negatively associated with hospitalization due to COVID-19 (p = 0.008) and the use of immunosuppressants (p = 0.032), siponimod (p < 0.001), and cladribine (p = 0.021). The pooled proportion of PwMS that reported any change of the employment status during the COVID-19 pandemic was 0.43 (95% CI = 0.36 -0.50) while the pooled prevalence of PwMS who worked remotely during this period was 0.37 (95% CI = 0.15 -0.58). The change in employment status was negatively associated with the duration of MS (p = 0.03) but positively associated with the progressive phenotype of the disease (p < 0.001).Our seminal review may serve as an example of how patients with neurological diseases or disabilities in general may have their jobs impacted in a pandemic and foster the context of global socio-economic crisis.